Automotive industry safety using virtual light communication - Abdullah, Muhamad Atif (2014)
Starting from the first ever car invented until now in the automotive industry, safety is the main issues highlighted especially involving consumer driving activities. Therefore, this study is an attempt in investigating and designing a new concept of technology for future car based on the Virtual Light Communication (VLC) technology that involves the developing technology for driveless car. The objective for this project is to design and develop new model in transmitting signal from a car to another car inters vehicle communication using the approach of virtual light conception. Moreover, there are three stage available in carrying out the systems element; sensing, controlling and notifying stages. The receiver sensing elements will wait until system receives the transmitting signal from the sensing stage. In the meantime, for the controlling part it will supervise the motor performance based on the transmitting and receiver signal. Hence, an indicator is us for notification stage will notify the current condition of vehicle. At the end of this project, the system has been successfully being designed, developed and tested at the prototype level for three stage of the system. More to the point, the system will starts to trigger the IR sensor whenever the digital input becoming HIGH which will respond to the mechanical output. Nevertheless, the IR transceiver required a 38 kHz modulated frequency to match the operating system of the transmitter and receiver.